Understanding blockchain for insurance use cases. (2020) - Popovic, D.; Avis, C.; Byrne, M.; Cheung, C.; Donovan, M.; Flynn, Y.; Fothergill, C.; Hosseinzadeh, Z.; Lim, Z.; Shah, J.
Abstract: Insurance industry practitioners have deep knowledge of their industry, but there is a lack of a simple-to-understand, practical blueprint on applying distributed ledger technology solutions, including blockchain. This paper provides a practical guide for actuaries, risk professionals, insurance companies and their Boards on blockchain, including an education piece to provide an understanding of the technology. Examples of real-world applications and use cases in insurance are provided to illustrate the capability of the technology. The current risks and challenges in adopting the technology are also considered. Finally, a checklist of issues to consider in adopting a blockchain solution for insurance business problems is provided.